Determination of anxiety, depression, and life satisfaction in lung cancer patients - Koç, Zeliha; Keskin Kızıltepe, Selin (European Journal of Oncology and Environmental Health, 2018)
Background and aim of the work: This study aimed to determine the life satisfaction of patients with lung cancer by examining their levels of anxiety and depression. Methods: The study group consisted of 108 patients with lung cancer who were inpatients in a university hospital located in the Middle Black Sea region of Northern Turkey. The study was conducted between 28 March  and 30 September 2013. Data were obtained using the Hospital Anxiety and Depression Scale (HADS) and Satisfaction with Life scale. Results: In this study, 3.7% of the patients were females, 96.3% were males, 96.3% were married, and 62.0% were primary school graduates. With regard to the disease stage, 40.7% were Stage 3. Among the group, 56.5% of the patients were receiving chemotherapy. In the patients, the treatment-related side effects were tiredness (78.7%), taste changes (68.5%), anorexia (65.7%), nausea (62.0%) vomiting (64.8%), and dyspnea (52.8%). According to the HADS scale, 97.2% of the patients had a risk of anxiety, and 100% had a risk of depression. The total score average of the patients on the Satisfaction with Life scale was 24.4±7.3. Conclusions: Almost all the patients had a risk of anxiety and depression. They were partially satisfied with their lives. They obtained relief from complementary and alternative treatments, such as biologically based therapies (herbs and dietary supplements) and mind-body control (prayer). The use of complementary and alternative treatments by lung cancer patients should be considered, as these may interfere with their prescribed treatment protocols.